2016
DOI: 10.1589/jpts.28.2393
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effect of hydraulic distension plus manual therapy on patients with frozen shoulder

Abstract: [Purpose] This study aimed to develop a clinical protocol for the treatment of frozen shoulder using applied hydraulic distension plus manual therapy. [Subjects and Methods] Patients were randomly assigned to 2 groups: 60 patients in group A were treated with hydraulic distension plus manual therapy, and 61 in group B were treated with hydraulic distension alone. Treatment effects were assessed using the Visual Analog Scale (VAS) (pain and satisfaction), and active range of motion of the shoulder (forward flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
1
Order By: Relevance
“…In the later stages, when there is persistent pain and stiffness, manipulation under anaesthesia is often associated with severe pain and mechanical complications such as fracture and subluxation of the joint. Some authors [17][18][19] have recommended hydrostatic pressure to rupture the capsule. De Palma [20] has suggested that, before manipulation, one should distend the joint with saline solution under pressure until free flow is established.…”
Section: Discussionmentioning
confidence: 99%
“…In the later stages, when there is persistent pain and stiffness, manipulation under anaesthesia is often associated with severe pain and mechanical complications such as fracture and subluxation of the joint. Some authors [17][18][19] have recommended hydrostatic pressure to rupture the capsule. De Palma [20] has suggested that, before manipulation, one should distend the joint with saline solution under pressure until free flow is established.…”
Section: Discussionmentioning
confidence: 99%
“…Considering a 0.05 two-sided significance level in each group, a power of 90% to detect a difference in mean SPADI values of ≥10 with a standard deviation of ≤15, and an allocation ratio of 1 : 1, 39 participants were required in each group. Allowing for a dropout rate of 20%, a total of 180 participants were included (90 participants in each group) [ 15 ]. Each participating clinical center treated 30 patients, comprising 15 in the control group and 15 in the treatment group.…”
Section: Methodsmentioning
confidence: 99%
“…At the end range of each, the patient is asked to resist further ROM by activating their muscles and holding this isometric contraction for 6–8 s. Comparable manipulations include Mulligan's technique and Gong's manipulation 25,26 . The addition of manipulation appears to provide faster and greater improvements in pain and ROM in the 3 months following the procedure 1,27–29 …”
Section: Case Scenariomentioning
confidence: 99%